Agriculture in development of select African countries : linkages with trade, productivity, livelihood and food security. - Fostering Equity and Accountability in the Trading System Project; CUTS Geneva Resource Centre (Geneva : CUTS International, CUTS Geneva Resource Centre, 2011)
Outcome of the Project, Fostering Equity and Accountability in the T rading System supported by William and Flora Hewlett Foundation.
Includes statistical tables.
Includes bibliographical references.
Also available on World Wide Web.
Keywords: Agriculture -- Economic aspects -- Africa; Food supply -- Africa; Agricultural productivity -- Africa; Agriculture and state -- Africa